2001
DOI: 10.1002/1521-3765(20010417)7:8<1703::aid-chem17030>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of a New Heck Reaction Mechanism Catalyzed by Palladium(II/IV) Species

Abstract: In this theoretical study on the Heck reaction we explore the feasibility of an alternative pathway that involves a PdII/PdIV redox system. Usually, the catalytic cycle is formulated based on a Pd0/PdII mechanism. We performed quantum chemical calculations using density functional theory on a model system that consisted of diphosphinoethane (DPE) as a bidentate ligand and the substrates ethylene and phenyl iodide to compare both mechanisms. Accordingly, the PdII/PdIV mechanism is most likely to occur in the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 50 publications
11
125
0
1
Order By: Relevance
“…Instead, it appears likely without further evidence that this low catalytic activity results from the catalysis of the (Pd(OAc) 2 + BQ) system via Pd 2+ /Pd 4+ . The Heck reaction mechanisms with palladacycles and other Pd 2+ compounds involving a Pd 2+ /Pd 4+ catalytic cycle have been advanced [26][27][28][29][30][31][32][33] and the formation of a transient palladacycle by the reaction of Pd(OAc) 2 with an olefin has been proposed [26]. In the present Heck reaction system with Pd/ SiO 2 (O), most of Pd 2+ /SiO 2 is practically converted to Pd 0 /SiO 2 that coexists with the remaining Pd 2+ /SiO 2 .…”
Section: Resultssupporting
confidence: 71%
“…Instead, it appears likely without further evidence that this low catalytic activity results from the catalysis of the (Pd(OAc) 2 + BQ) system via Pd 2+ /Pd 4+ . The Heck reaction mechanisms with palladacycles and other Pd 2+ compounds involving a Pd 2+ /Pd 4+ catalytic cycle have been advanced [26][27][28][29][30][31][32][33] and the formation of a transient palladacycle by the reaction of Pd(OAc) 2 with an olefin has been proposed [26]. In the present Heck reaction system with Pd/ SiO 2 (O), most of Pd 2+ /SiO 2 is practically converted to Pd 0 /SiO 2 that coexists with the remaining Pd 2+ /SiO 2 .…”
Section: Resultssupporting
confidence: 71%
“…DFT calculations have, however, established that the oxidative addition of iodobenzene with a Pd(II) complex is energetically not favoured at all [58]. Some Mizoroki-Heck reactions proceed with an induction period when the base is a tertiary amine [55b], but no induction period is observed when an acetate salt is used as a base [27,55].…”
Section: Pd(0) Formation From a Pc-palladacyclementioning
confidence: 99%
“…Previous computational studies employing bis-ligated palladium have found similar g 2 -arene complexes and oxidative addition transition states to those reported here [23,[25][26][27]. The most directly comparable study is that of Cundari and Deng [28] who model the catalytic cycle for Pd(PH 3 ) and Pd(PH 3 ) 2 .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The majority of these involve bis-phosphine palladium catalysts [23][24][25][26][27]. Cundari [28] has recently reported a density functional study based on BuchwaldÕs work [29][30][31] with very bulky phosphines that compares mono-and bis-phosphine palladium moieties as catalysts [28].…”
Section: Introductionmentioning
confidence: 99%